Polymorphisms of estrogen receptor-α gene in Brazilian women with high breast density after menopause - Souza, Marilene Alícia; Fonseca, Angela Maggio; Bagnoli, Vicente R.; Barros, Nestor De; Franzolin, Solange O.B. [UNESP]; Carvalho, Katia C.; Soares-Jr, José Maria; Baracat, Edmund C. (Taylor & Francis, 2013)
The association of genetic polymorphism in the estrogen receptor alpha (ERα) gene and risk for diseases including breast cancer (BC) has been the subject of great interest. Objective: Checking on women with high breast density after menopause, the frequency of the Pvull and Xbal polymorphisms of the ERα gene and the correlation between them and the known risk factors for breast cancer. Method: Observational study with 308 women between 45 and 65 years old with high breast density, without hormonal therapy, menstruation for a year or more, breast and ovarian cancer history. It was characterized in clinical history and physical examination: menarche, menopause, parity, family history of BC, smoking, alcohol intake and body mass index. Results: The allelic and genotypic frequencies for ERα-Pvull and Xbal: p=43.99%; p=56.01%; pp=32.14%; Pp=47.73% and PP=20.13%; X=41.56%; x=58.44%; xx=33.44%; Xx=50.00% and XX=16.56%, respectively. The most frequent risk factors for BC: menarche before 12 years old (35.38%), nulliparity or first child after 28 years old (41.66%), family history of BC (19.16%) and overweight/obesity (62.01%). Conclusion: Allelic and genotypic distribution similar to literature. The risk factors for BC were more prevalent in women with high breast density but without significant associations with these polymorphisms. © 2013 Informa UK Ltd. All rights reserved.
Keywords: Breast neoplasms; Estrogen receptors; Genetic polymorphism; Mammography; Risk factors; estrogen receptor alpha; protein; Pvull protein; unclassified drug; Xbal protein; adult; aged; alcohol consumption; body mass; Brazil; breast; breast cancer; breast density; cancer risk; Caucasian; density; family history; female; gene frequency; genetic association; genetic polymorphism; genetic risk; genotype; homozygote; human; major clinical study; medical history; menarche; menopause; menstruation; mutation rate; nullipara; obesity; observational study; organ size; ovary cancer; parity; physical examination; priority journal; smoking